Crusading peace : Christendom, the Muslim world, and Western political order - Mastnak, Tomaž (University of California Press, 2002)
Tomaz Mastnak's provocative analysis of the roots of peacemaking in the Western world elucidates struggles for peace that took place in the high and late Middle Ages.